Research and theory into practice: Australian preservice teachers' knowledge of evidence-based early literacy instruction. Issue 2 (2nd July 2020) - Meeks, Linda; Madelaine, Alison; Kemp, Coral
ABSTRACT: Much has been written about the decline in Australian literacy standards, as measured by international tests, and concerns have been expressed about the quality of teacher preparation for teaching early literacy to young children in their first years of school. Preservice teacher knowledge of research evidence supporting the essential components of early literacy instruction and the strategies used to teach these foundation skills are explored in this study. Responses to survey questions provided both quantitative and qualitative data. Results suggest that although preservice teachers have some knowledge of the components of early literacy identified in research, they are less knowledgeable about the subject-specific pedagogical strategies identified as necessary for implementing evidence-based practices. These results are not surprising given the findings of recent research into the quality of literacy units in teacher education courses.